Impact of nonsynonymous single nucleotide polymorphisms in PROCR gene on protein stability and thrombotic risk: a molecular dynamic approach - Abuagla, Hytham Ahmed; Adam, Khalid Mohamed; Elangeeb, Mohamed E.; Ahmed, Elsadig Mohamed; Ali, Elshazali W.; Edris, Ali M.; MohamedAhmed, Abubakr Ali Elamin; Eltieb, Elmoiz Idris; Khalid, Tarig Babikir Algak; Elamin, Bahaeldin K.; Osman, Hiba Mahgoub Ali; Idris, Ebtehal Salih (Frontiers in Genetics, 2025)
IntroductionThrombosis is a serious vascular disorder influenced by genetic factors, including nonsynonymous single nucleotide polymorphisms (nsSNPs) in the PROCR gene, which encodes the endothelial protein C receptor (EPCR). These mutations may disrupt EPCR stability and impair its anticoagulant function, thereby increasing the risk of thrombosis.MethodsWe employed a multi-layered computational approach to analyze 217 nsSNPs in the PROCR gene. Functional impacts were predicted using Sorting Intolerant From Tolerant (SIFT), Polymorphism Phenotyping v2 (PolyPhen-2), Screening for Non-Acceptable Polymorphisms 2 (SNAP2), and Protein Analysis Through Evolutionary Relationships (PANTHER). Disease associations were assessed using Single Nucleotide Polymorphisms and Gene Ontology (SNP&GO) and Predictor of Human Deleterious Single Nucleotide Polymorphisms (PhD-SNP). Protein stability was evaluated using I-Mutant and MUpro, while structural implications were analyzed with Mutation Prediction (MutPred), ConSurf, and Have Our Protein Explained (HOPE). Active binding sites were identified using PyMOL. Finally, 100-nanosecond molecular dynamics (MD) simulations were conducted using GROningen MAchine for Chemical Simulations (GROMACS) to compare structural deviations, flexibility, and solvent interactions between wild-type EPCR and key mutant proteins.ResultsOur integrated analysis identified three high-risk nsSNPs—T174I, N136I, and L168P—that detrimentally affect EPCR function. These variants disrupt critical glycosylation sites, α-helix integrity, and catalytic residues, leading to increased root mean square deviation (RMSD) and root mean square fluctuation (RMSF), reduced hydrogen bonding, and higher solvent-accessible surface area (SASA) in mutants compared to the wild-type. Disease association tools further linked these mutations to an elevated thrombotic risk.DiscussionThese findings suggest that the identified nsSNPs destabilize EPCR by altering its structural dynamics and reducing its capacity to activate protein C. This provides mechanistic insight into how PROCR variation may contribute to thrombotic disorders and highlights the utility of in silico approaches for prioritizing potentially pathogenic variants.ConclusionOur study demonstrates that deleterious nsSNPs in the PROCR gene can significantly impair EPCR stability and function, thereby increasing susceptibility to thrombosis. These findings provide a foundation for future experimental validation and may inform the development of personalized therapeutic strategies for managing thrombotic disorders.